The Consequences of Extending Equitable Property Division Divorce Laws to Cohabitants - Abraham Chigavazira; Hayley Fisher; Tim Robinson; Anna Zhu (Institute of Labor Economics (IZA), 2019)
This paper analyses the effect of extending equitable property division divorce laws to unmarried cohabiting couples in Australia. Using a triple-difference fixed effects approach we show that existing couples are more likely to make relationshipspecific investments after being exposed to laws enabling the equitable redistribution of property in the event of relationship breakdown. In affected couples we find that men increase their employment and women increase time spent on housework. Couples have more children and are more likely to become home owners. These results demonstrate the causal effect of property division laws on relationship-specific investments and inform the ongoing international debate about the appropriate legal treatment of unmarried cohabiting couples.
Keywords: J12; K36; 330; cohabitation; divorce; property; division; household behavior